Comprehension of Reading Content Using Skimming Techniques to Improve Comprehension of Narrative Text Reading Content in Elementary School Students: Pemahaman Isi Bacaan Dengan Menggunakan Teknik Skimming Dalam Meningkatkan Pemahaman Isi Bacaan Teks Narasi Pada Siswa Sekolah Dasar - Shovana Aulia Paramitha; Kemil Wachidah (Academia Open, 2021)
This study aims to determine the effect of using skimming techniques and describe the use of skimming techniques in understanding the reading content of elementary students. This study uses the System Literature Review (SLR) research method. From the results of several studies that have been successfully reviewed, it shows that the use of skimming techniques in understanding reading content is the right technique to use in understanding reading content because skimming techniques can increase students' knowledge of reading more. The use of skimming techniques can be done in the first way, having questions to look for, reading book titles and subtitles, reading with rapid eye movements, understanding sentences in the reading, then being able to draw conclusions. Based on the analysis that has been done, it can be concluded that the use of skimming techniques has a very good effect on students 'reading comprehension and can be an alternative or method to help improve reading content comprehension and broaden students' knowledge.